Melihat pergeseran struktur perekonomian jawa timur selama pandemi covid-19 dengan Analisis Shift Share - Oeliestina, Oeliestina (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The Covid-19 pandemic has harmed the economy. In 2020 the Indonesian economy contracted by 2.07 percent. Likewise, East Java Province, contracted by 2.07 percent. Whereas East Java is the second largest contributor to the economic pie at the national level. The percentage of East Java's GRDP reached 14.48 percent. The pandemic has the potential to change the economic structure of East Java. This shift will certainly have an impact on the Indonesian economy. For this reason, a study is needed on the impact of the Covid-19 pandemic and the shifts that have occurred in the economic structure of East Java. So that policies can be taken as part of mitigation against sectors that have slumped during the Covid-19 pandemic. The methodology used in this research is descriptive and Shift Share (SS) analysis. The results of the calculation of the Net Shift (PB) in the Shift Share (SS) economic growth profile analysis quadrant map interpret that there are nine progressive sectors and eight conservative sectors. While the leading sectors that were able to survive during the Covid-19 pandemic were two sectors, namely the real estate sector and education services. We need full support for the progressive sector and maximum encouragement for the conservative sector to get up soon